Improving The Domestic Product Use Policy For Ministerial Procurement In Indonesia - Ananta, Iqbar Diaz; Qadri, Resi Ariyasa (PT WIM Solusi Prima, 2024)
The objective of this study is to devise an evaluative framework, encapsulated as a checklist of inquiries, aimed at refining the implementation of Domestic Product Utilization Policies (P3DN). This investigation addresses the conspicuous absence of a structured framework for evaluating the enforcement of P3DN within the context of governmental procurement activities across ministries and institutions in Indonesia. Employing a qualitative methodology, this study undertakes thematic analysis of the regulations governing the procurement of goods and services. This analysis is enriched by insights derived from interviews with procurement specialists, contributing to the framework's development. The evaluative mechanism is predicated on a “value for money” paradigm, assessing the procurement process in terms of inputs, outputs, and outcomes to anchor the framework's evaluative criteria. The research contributes to the creation of a comprehensive checklist, envisioned as a practical tool for ministries and institutions to systematically appraise the implementation of P3DN within their procurement processes. From an academic standpoint, this research advances scholarly understanding in the domain of public procurement management, contributing a novel evaluative instrument that enhances both theoretical and practical approaches to policy assessment within the public sector's procurement practices.